AN ANALYTICAL STUDY OF ALEKSANDR FAYNBERG’S POEM “LOOK FROM THE BOTTOMLESS SEA” - Zoirova Diyora, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Introduction. Modern Uzbek–Russian poetry has long been enriched by poets who explore the human  spirit,  the  subtle  shades  of  emotion,  and the symbolic  relationship  between nature and the inner world. Among such prominent figures stands Aleksandr Faynberg (1946–2021),  a  poet  widely  known  for  his  gentle  lyricism,  spiritual  depth,  and universal  humanistic  worldview.  His  works  often  merge  personal  experience  with abstract reflections on life, time, and memory, creating a poetic landscape where nature acts as both companion and witness to human emotion. The poem “Look from the Bottomless Sea” (Tubi yo‘q dengizdan boq) presents one of Faynberg’s most delicate lyrical meditations. Through natural images such as the sea, stars, leaves, and wind, the poet constructs a symbolic dialogue between the lyrical  hero  and  the  world.  The  poem  is  not  merely  descriptive;  it  reveals  a  deep emotional  structure  in  which  poetry  becomes  a  space  for  spiritual  purification  and connection with future generations.